Impact of cerebrovascular stroke on inflammatory periodontal indices: a systematic review with meta-analysis and trial sequential analysis of case-control studies - Dioguardi, Mario; Bizzoca, Maria Eleonora; Cantore, Stefania; Caloro, Giorgia Apollonia; Musella, Gennaro; Mastrangelo, Filiberto; Lo Muzio, Lorenzo; Ballini, Andrea (Frontiers in Oral Health, 2024)
IntroductionCerebrovascular stroke, a leading cause of global morbidity and mortality, is influenced by several modifiable risk factors such as hypertension, diabetes, and smoking. Emerging evidence highlights the significant role of inflammation in stroke pathogenesis, with conditions like periodontitis potentially exacerbating this risk. The aim of this systematic review was to identify and quantify the real impact of periodontal disease in individuals with cerebral stroke through the analysis of inflammatory periodontal indicesMethodsFollowing PRISMA guidelines, we conducted a systematic review and meta-analysis of case-control studies assessing periodontal indices in stroke patients. Data sources included PubMed, Scopus, and Cochrane Library, with searches extended to grey literature. The review protocol was registered on PROSPERO (CRD42024529767). Studies were evaluated using the Newcastle-Ottawa Scale to assess risk of bias, and meta-analyses were conducted using Review Manager 5.4 and TSA software.ResultsThe review included seven case-control studies, comprising 723 stroke patients and 787 controls. Meta-analyses revealed significant differences between stroke and control groups in clinical attachment loss [MD 1.04 mm, 95% CI (0.54, 1.54)], probing pocket depth [MD 0.68 mm, 95% CI (0.31, 10.6)], and radiological bone loss (MD 2.15 mm, 95% CI [−1.58, 5.89]. These findings indicate that stroke patients exhibit worse periodontal health compared to controls, supporting a potential link between periodontal inflammation and stroke.ConclusionThis study confirms the significant impact of periodontal disease on stroke patients and highlights the importance of oral health in preventing adverse cerebrovascular events.Systematic Review RegistrationPROSPERO, identifier (CRD42024529767).